Ecocentrism as Reconciliation of The Exploitation of Women and Nature by Capitalist Anthropocentrism: A Review of The Interpretation of Al-Tahrir wa Al-Tanwir - Juliani Syafitri; Siti Mariam Ulfah (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2024)
The concept of ecocentrism as a rehabilitation of the exploitation of nature and women becomes important in the midst of the onslaught of ecological disasters caused by the capitalist anthropocentrism of this era. Just as nature, women are among the victims because women and nature are often symbolized in similar ways in many respects. Ecocentrism plays a crucial role because it offers holistic justice for all elements of the natural world. The focus of this research is Ibn Asyur's interpretation in "Tafsir al-Tahrir wa al-Tanwir," which presents an ecocentric ecological study. The research method used is the thematic interpretation method with a descriptive analysis approach. This study explores verses that contain ecocentric content and shifts away from the paradigm of capitalist anthropocentrism. The results of this research find that there are similarities between the principles of ecocentrism and the Quranic verses, namely: 1) Surah Al-Isra, verse 44, and Al-An'am, verse 141, which state that all creatures glorify Allah, and the Earth has its own beauty. 2) Surah Al-A'raf, verse 31, which prohibits excessive exploitation of other beings, as Allah does not like excessive behavior. 3) Surah An-Nisa, verse 9, which emphasizes that humans should prepare the best generation rather than focusing solely on quantity when managing nature. 4) Surah Ar-Rum, verse 41, which warns that the harm caused by humans will bring punishment from Allah. 5) Surah Al-Baqarah, verse 30, which highlights that humans, as stewards, should make policies that benefit all aspects of life.